(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
2019 has been challenging for everyone as people faced the COVID-19 pandemic. The severe short-term description felt by many employees and people around the globe, including the fast food chain delivery services in Barangay Greater Largo, Quezon City. Lockdown has been challenging for people around the world, especially fast food chain employees, due to the increased risk of getting COVID-19. Yet, food deliveries in fast food chains can still be productive during the pandemic with technology. This health crisis has introduced uncertainty in major national and global society aspects. Due to the uncertainties and lockdowns brought on by the pandemic, people cannot eat outside (Jollibee, McDonald’s, Mang-inasal) because of applications such as Grab, Food Panda, etc. It helped the economy greatly amidst the pandemic. It also helped those who lost their jobs during the pandemic as they became food delivery riders. In Barangay Greater Lagro, Quezon City, the researchers conducted a study to ascertain the effect of COVID-19 on fast food chain delivery services. This research applied the descriptive method design for the scrutiny of the study. The researchers collected data with the help of Google Forms, which met the following criteria: thirty-four (34) household customers, thirty-three (33) management employees, and thirty-three (33) food delivery riders with a total number of one hundred (100) target respondents. The survey results reveal that most of the respondents are in the age group of 19-23, mostly male. In the recruitment done, it was found that 96% of the respondents agreed that having food delivery applications and food delivery services is effective even amid the pandemic, while 4% disagreed. However, it shows the importance of how this helped the economy in the said industry. Based on the gathered data, recommendations were formulated for the betterment of the industry while facing the pandemic. Recommendations were offered, including the safety of the service delivery riders and the further use of different platforms and applications to help the industry grow. The problems encountered by the respondents are strict health protocols, health risks faced by the employees, and limited customer service. The study implies that the fast-food chain industry needs to adapt to the current situation and use technology to continue its operations.